Strategi Kepemimpinan Kepala Sekolah dalam Membangun Sekolah yang Berkualitas dan Berdaya Saing - Muhammad Bagas Hidayatullah; Allyah Zahirah; Radit Septa Wijaya; Syriffudin4 Syariffudin (Jurnal Ilmu Sosial dan Humaniora, 2026)
Education plays a crucial role in improving the quality of human resources and supporting national development. In the context of schools, the leadership of the principal is one of the key factors determining the success of the educational process. This study aims to analyze the leadership strategies of school principals in developing high-quality and competitive schools. The research employed a qualitative approach using a library research method. Data were collected from various sources of literature, including books, scientific journals, articles, and other relevant documents related to the research topic. The findings indicate that principals have a strategic role in improving the quality of education through various leadership strategies, such as enhancing teachers’ competencies through training and professional development, fostering a positive school culture, and implementing effective school management. In addition, principals also function as motivators who are able to establish strong working relationships with teachers and create a supportive and conducive work environment. Effective leadership strategies contribute to improving teacher performance, the quality of learning, and student achievement. Therefore, effective principal leadership plays a vital role in developing schools that are high-quality, competitive, and capable of responding to the challenges in the field of education.